ANALISIS KINERJA PEGAWAI DALAM MEMBERIKAN PELAYANAN PRIMA PADA MASYARAKAT DI KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Anjani, Tria; Samosir, Suhaila Husna (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2021)
This study aims to determine the analysis of employee performance in providing excellentservice to the community in Perbaungan District, Serdang Bedagai Regency. This study usesa SWOT approach, aims to determine the performance of employees in providing excellentservice to the community in Per baungan District, Serdang Bedagai Regency. The populationof this study was the Head of the Sub Sub-district Head, Employees and the Community ofPerbaungan District, Serdang Bedagai Regency, as many as 30 people. The analysistechnique used is SWOT analysis. From the results of the internal – external matrix obtainedfrom the total value of the weighting score on the improvement strategy, the internal factor isworth 0.625, which means this value is the difference between strengths and weaknesses. Andfor exte rnal factors it is worth 0.205, which means this value is the difference betweenopportunities and threats, where the threat value is the same as the opportunity. EmployeePerformance Analysis in Providing Excellent Service to the Community in PerbaunganDistrict, Serdang Bedagai Regency, is in quadrant I (Aggressive Strategy). The situation inthis increase is situation I, which is a situation where the strategy that must be taken in thiscondition is to support an aggressive growth policy or growth orient ed strategy by takingadvantage of existing opportunities and the internal strengths of the sub sub-district office.